Application of Soy, Corn, and Bean By-products in the Gluten-free Baking Process: A Review - Egea, Mariana Buranelo; De Sousa, Tainara Leal; Dos Santos, Daiane Costa; De Oliveira Filho, Josemar Gonçalves [UNESP]; Guimarães, Rafaiane Macedo; Yoshiara, Luciane Yuri; Lemes, Ailton Cesar (Springer Nature, 2023)
Grain by-products, normally rich in dietary fiber and bioactive compounds, are important for the human diet and have been studied as potential raw materials for the development of gluten-free products. Thus, the purpose of this review is to provide a background on the challenges of producing gluten-free bakery products using soy, corn, and bean by-products, which stand out as products of great economic importance. The use of these by-products improves the nutritional profile (the content of proteins, fibers, and phenolic compounds, among others) in bakery products, but it can also have a positive or negative effect on technological properties (color, texture, volume, porosity, thickness, homogeneity, etc.) and mainly in sensory characteristics; therefore, they must be well understood to establish adequate technological processes. In general, the use of grain by-products as functional ingredients for the development of gluten-free bakery products is promising due to their low cost and nutritional characteristics, contributing to the development of healthy products for the consumers. In addition, despite changes in technological characteristics and sensory characteristics, the use of by-products makes it possible to diversify foods and reduce the costs of foods for celiac people who mostly face difficulties in adapting their diet. Additionally, the use of by-products can contribute to the mitigation of negative environmental impacts and create more advantageous applications.
Keywords: Celiac disease; Corn bran; Functional foods; Okara flour; Sensory profile; Sustainability; Technological properties